What drives firms' decisions to spend on environmental protection? - Iulia Siedschlag; Weijie Yan (The Economic and Social Research Institute (ESRI), 2020)
This paper examines factors underlying firms' capital and current expenditures on environmental protection. Using microdata from Ireland's industry sector over the period 2008-2016, we analyse a range of such factors including firm characteristics, environmental regulations, competition and spillover effects from firms with investment and spending on environmental protection within the same industry or within the same region. Our results indicate that larger firms, importers, and firms which are part of an enterprise group are more likely to invest in equipment for pollution control and in equipment linked to cleaner technologies. Industry competition incentivises firms to invest in equipment for cleaner technologies. Further, our results indicate that the propensity of firms to invest in equipment for pollution control and to spend on environmental protection are higher for more energy-intensive firms. Finally, our results uncover significant positive spillover effects from firms with capital expenditures as well as from firms with current expenditures on environmental protection in the same industry or the same region on firms' decisions to invest and spend on environmental protection.
Keywords: D22; F23; L21; L53; Q55; 330; Corporate expenditures on environmental protection; environmental regulations; peer effects; multinational activity